If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = 9x + -2 Reorder the terms: 10 + 3x = 9x + -2 Reorder the terms: 10 + 3x = -2 + 9x Solving 10 + 3x = -2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 10 + 3x + -9x = -2 + 9x + -9x Combine like terms: 3x + -9x = -6x 10 + -6x = -2 + 9x + -9x Combine like terms: 9x + -9x = 0 10 + -6x = -2 + 0 10 + -6x = -2 Add '-10' to each side of the equation. 10 + -10 + -6x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + -6x = -2 + -10 -6x = -2 + -10 Combine like terms: -2 + -10 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| (2x-3)/(5x-1) | | 43-2=13x-83 | | 2x+54=-21+x | | -28=4/5d | | -36x^2+4=0 | | 14x-28=24-12x | | n+14=11 | | 3(y+7)(-y-2)=0 | | 10+7n=5-6 | | 14/z=9-z | | 4x+9=180 | | 8x-66=36+2x | | x+-9=15 | | x^2+3x+756=0 | | 64=8y | | Cos(2x)+sin(2x)=0 | | 3.3+3.83= | | An=2A | | (8-v)(2v+5)=0 | | 21+c=30 | | r^2+42r=0 | | 380=2(w+1)+2(w+20) | | 4x+2(16/5)=8 | | (z+6)(z+9)=0 | | 8x^2-56x+98=0 | | X-21=2x+87 | | -4=13+b | | (6x+1)-2x=5 | | 3t+10-7t+5t= | | 1/5x=12 | | 2p-1=4p+3p-6 | | (3x+7)(4y-5)= |